Distribution and Conservation of Less Known Rare and Threatened Plant Species in Kachchh, Gujarat, India - Joshi, Pankaj N.; Soni, Hiren B.; Sunderraj, S.F. Wesley; Joshua, Justus (Our Nature, 2014)
The present survey was conducted in different terrains, habitats and ecosystems of Kachchh, Gujarat, India, for consecutive 3 years (2001-2002) in all possible climatic seasons, to know the present status of 6 less known rare and threatened plant species viz., Ammannia desertorum, Corallocarpus conocarpus, Dactyliandra welwitschii, Limonium stocksii, Schweinfurthia papilionacea and Tribulus rajasthanensis. Distribution, abundance and population dynamics of these species were derived. DOI: http://dx.doi.org/10.3126/on.v11i2.9541 Our Nature 2013, 11(2): 152-167